A new Simulation Model for Grate Firing Systems in OpenFOAM. (1st February 2021) - Rückert, Frank Ulrich; Lehser-Pfeffermann, Daniel; Theis, Danjana; Kim, Ju Pyo; Schargen, Andre; Zorbach, Ingo; Sohnemann, Jens
Abstract: A grate firing system can be seen as a multiphase flow problem. High volume fractions of solid fuel particles travel over the grate of a power plant, while heterogeneous reactions occure at the surface of the particles in combination with homogeneous combustion reactions inside the flue gas. Up to now, grate firing systems are still difficult to simulate with standard computational fluid dynamics (CFD). The movement of the solid particles inside the fuel bed and their heterogeneous reactions are difficult to combine with the homogeneous reactions of the gas phase species and the heat transfer. The emitted radiation from the gas has to be coupled with the heat balance inside the fuel bed. To solve this problem, we integrated a new library into a open source CFD code for coupling radiation models with the solids phase. We describe how to handle the workflow of the new library and present simulation results for two different furnace designs. An automatic mesh generator was developed. The work closes with simulation results for two different grate firing systems. Heterogeneous reactions and homogeneous reactions, as well as temperature fields inside the phase are presented. A validation of the simulations against measurement data is given. Highlights: Simulations models for power plants are necessary in the early design phase. Sustainable and climate-friendly combustion process for waste or biomass. Modelling of drying, pyrolysis, char burnout and gas phase reactions. Advanced radioation models and Eulerian particle model describe heat transfer. Designs of grate firing systems and discretisations can be generated automatically.